A Significantly Twisted Spirocyclic Phosphine Oxide as a Universal Host for High‐Efficiency Full‐Color Thermally Activated Delayed Fluorescence Diodes. Issue 16 (29th February 2016) - Li, Jing; Ding, Dongxue; Tao, Youtian; Wei, Ying; Chen, Runfeng; Xie, Linghai; Huang, Wei; Xu, Hui
Abstract : A universal thermally activated delayed fluorescence (TADF) host, 4′‐diphenylphosphinoylspiro[fluorene‐9, 9′‐xanthene] (SFXSPO), is constructed with a highly distorted and asymmetric configuration and disordered molecular packing in its solid state. SFXSPO successfully endows its full‐color TADF diodes with state‐of‐the‐art performance, e.g., the record external quantum efficiency of 22.5% and 19.1% and internal quantum efficiency of ≈100% for its yellow TADF diodes and single‐host full‐TADF nearly‐white‐emitting devices, respectively.